IDENTIFIKASI PERMASALAHAN BIOFISIK DAN SOSIAL EKONOMI DI MODEL DAERAH ALIRAN SUNGAI MIKRO (MDM) BATANG TEGAN - Rudi Hartawan (Universitas Batanghari Jambi, 2014)
In the framework of the management of the river basin (DAS) to develop a model of watershed management in small extents (DAS Micro) will be able to accommodate the needs of sustainable watershed management objective that includes the object biophysical, social, economic, and institutional. Watershed management should be integrated from upstream to downstream areas involving all parties associated with the principle of one river, one plan and one integrated organization. Micro DAS Stem Tegan is part of the Sub Watershed Batang Bungo who was instrumental for the Dusun community Rantau Pandan and LUBUK Wood Aro in Sub Region Senamat Ulu Pandan and Orchard and Orchard Muaro Make The heart of the District III Ulu Muaro Bungo District, Jambi Province. Sustainability of the river is very important this river is a placeholder from catcment area dominated by land titling 25-40% (rather steep) with extents 1868.88 Ha. The main potential biophysical land areal MDM is a District Snapshot water (DTA) or Catchment Area. Micro DAS Stem Tegan is pensuplai water to Sub DAS further Batang Bungo will join the DAS Batanghari. Biophysical problems onto the areal MDM is low soil fertility, soil erosion splash and sheet type, slope of land, availability of critical land and the land has the potential to become critical. The main potential of the social economy of institutional structures are formed community orchard, potential productive workforce, there is a means of education, worship, health, as well as some economic institutions such as markets and society. Social and economic problems that are being recorded from areal MDM is a high rate of population growth, poverty, and dependence of agricultural land.Keywords: Soil and water conservation and cultivation zones